The health quality of the diet and selected health indicators of Polish e-sports players - Mazur-Kurach, Paulina; Gacek, Maria; Pięta, Aleksandra; Frączek, Barbara (Frontiers in Nutrition, 2026)
IntroductionDiet is one of the important factors affecting health and physical performance. The aim of the study was to assess the relationship between the health quality of the diet and selected health indicators in a group of Polish e-sports players training at a professional and semi-professional level. The hypothesis was that a higher quality diet is associated with more favorable health indicators in e-sports players.MethodologyThe study was conducted among 174 men aged 18–28 years, assessing anthropometric characteristics, morphological and biochemical blood biomarkers, and two markers of intestinal permeability in faeces. The Beliefs and Eating Habits Questionnaire KomPAN was used to assess diet quality. Statistical analysis of the relationships between diet quality indicators and health indicators was performed using Spearman’s rank correlation and principal component analysis (PCA) and multiple regression, assuming a test probability of p < 0.05.ResultsThe study group was dominated by e-sports with low levels of healthy diet indicators pHDI-10 (approx. 96%) and unhealthy diet indicators nHDI-14 (approx. 86%) and low overall diet quality DQI-24 (approx. 96%). Among the health indicators assessed, a low percentage of e-sports players had normal levels of uric acid and glucose in their blood (approx. 69 and 64%, respectively) and zonulin and lipopolysaccharides (LPS) in their faeces (37 and 28%, respectively). The Body Mass Index (BMI) was within the normal range for 60% of the group. Statistical analysis showed that the pHDI-10 index was significantly positively associated with vitamin D (R = 0.18) and HDL cholesterol (R = 0.19) and negatively with uric acid (R = −0.18) and blood glucose (R = −0.21) levels. The nHDI-14 index showed no significant associations with the analysed health indicators. However, the overall diet quality index DQI-24 was significantly negatively associated with uric acid levels (R = −0.18) and blood glucose (R = −0.23).ConclusionA low level of dietary health quality, varied health indicators and significant correlations between dietary quality and certain health indicators were demonstrated, suggesting a positive impact of a high-quality diet on the health of Polish e-sports players.